POETRY AND STUDENTS' READING ENGAGEMENT: An Exploratory Study In An Efl Classroom At A Senior High School In Bandung - Arsyad, Rahma (2013)
This study investigated the use of poetry as materials in an EFL classroom at school settings. It explored the students' engagement in learning through poetry and their responses to the use of poetry in EFL reading. This study used a qualitative-exploratory approach, involving 27 students of grade X of a senior high school in Bandung, West Java. Multiple data collecting techniques including observations, students' documents (written responses) and open-ended interviews identified that: (1) students were engaged in three ways namely behavioral, emotional and cognitive engagements. The students behaviorally invested their effort to comprehend poems learned through insightful reading and active participation in the class. Also, poetry engaged students' emotion that students expressed through affective reaction and responses. In the cognitive side, students had invested their high cognitive thinking through giving various analysis especially figurative analyses, associative and emotional responses. (2) Most students' responses to the use of poetry in reading class were positive. They admitted that poetry had given them many benefits especially in developing their vocabulary and promoting independent participation and critical thinking. With the reference to the result, it is suggested that poetry should be used appropriately as materials in EFL reading class to engage students in learning. There are also many aspects, such as students' competences and characteristics, to think about when teachers intend to use poetry as materials. It is because poetry is very sensitive. Inappropriate selection of poems and teaching method can be unprofitable for learning. It is also hoped that further in-depth studies can be conducted to get more insightful understanding on the use of poetry at school level. Key words: Poetry, Reading Engagement, EFL classroom Studi ini meneliti tentang penggunaan puisi sebagai materi pembelajaran bahasa Inggris di sekolah. Study ini mengeksplorasi engagement siswa dalam belajar melalui puisi dan respon mereka terhadap penggunaan puisi dalam EFL Reading. Studi ini menggunakan pendekatan qualitative-exploratory yang melibatkan 27 siswa tingkat X di salah satu SMA di Bandung, Jawa Barat. Dengan beberapa teknik pengumpulan data berupa observasi, dokumen siswa dan wawancar ditemukan bahwa: (1) siswa terlibat dalam tiga pola belajar yaitu behavioral, emotional and cognitive engagements. Secara behavioral, siswa menginvestasikan usaha mereka dalam memahami puisis melalui pembacaan yang mendalam dan partisipasi aktif di kelas. Secara emosional, siswa melibatkan diri melalui reaksi-reaksi dan respon afektif. Secara kognitif, siswa menginvestasikan pola berfikir yang tinggi (high cognitive thinking) melalui analysis figuratif, assosiatif dan emotif. (2) Respon siswa terhadap penggunaan puisi pada umumnya bersifat positif. Mereka mengatakan bahwa penggunaan puisi memberikan banyak manfaat khususny dalam mengembangkan kosakata, dan menstimulasi partisipasi yang independen serta berfikir positif. Berdasarkan hasil yang ditemukan, dapat disarankan bahwa puisi dapat digunakan sebagai materi EFL reading di tingkat sekolah. Namun, ada bebrapa hal yang perlu diperhatikan dalam pemilihan puisi yaitu karakteristik siswa berupa kemampuan dan karakter mereka karena puisi sangat sensitive. Pemilihan puisi dan metode pembelajaran yang tidak sesuai bisa memberikan dampak yang tidak baik bagi pembelajaran. Diharapkan pula penelitian lebih mendalam dengan ranah serupa dapat dilakukan agar informasi yang ditemukan bisa lebih dalam. Key words: Poetry, Reading Engagement, EFL classroom